Hybridization between Anguillicola crassus and A. novaezelandiae, and viability of the F1 generation. (18th March 2022) - Honka, K.I.; Grabner, D.; Sures, B.
Abstract: For decades, it has remained unclear how the Asian swim bladder nematode Anguillicola crassus was able to supplant the previously stable population of its relative from New Zealand Anguillicola novaezelandiae in the Lake Bracciano, Italy. Previously, researchers have hypothesized that A . crassus possesses an ecological advantage due to a more efficient life cycle in combination with a pattern of unidirectional hybridization between A . novaezelandiae females and A . crassus males. The present study focuses on the viability of hybrid offspring and their allelic pattern, particularly in developed adult stages of the hybrid F1 generation. While the percentages of hybrid individuals from A . novaezelandiae mothers and A . crassus fathers increased from egg to adult stages, it was more distinct in egg stages of A . crassus females and A . novaezelandiae males, but did not occur in adult F1 individuals at all. Therefore, we corroborate the hypothesis of unidirectional hybridization by differentiating between egg and adult stages, and suggest this as another explanatory factor for the extinction of A . novaezelandiae in Lake Bracciano in Italy and the predominance of A . crassus .